FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN COMPUTER VISION SYNDROME (CVS) PADA PEKERJA RENTAL KOMPUTER DI WILAYAH UNNES (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
Computer as a tool that is widely used human beings, it also raises occupational diseases as well as the use of machine in industry. Vision problems caused bye the use of computers, the American Optometric Association (AOA) called Computer Vision Syndrome (CVS) as a compound eye problems related to employment experienced by a person at close range as or related to computer use. The purpose of this study was to analyze the relationship between the working length, the distance eye with the monitor, lighting intensity, work attitude, and identifity the incidence of complaints of CVS workers experienced computer rentals. This study used Cross Sectional approach. Number of population and sample of 36 peoples working computer rental in the area Unnes campus. The instruments used in the form of quetionnatires, meter, and Lux meter. Chi square test result : (1)the working length (p=0,005); (2) the distance eye with the monitor (p=0,012); (3) lighting intensity (p=0,001); (4) work attitude (p=0,014) with complaints of CVS in workers computer rental at the campus Unnes. Suggestion for worker is to check their eyes regulary to the doctor if the complaints of CVS in order to minimize the occurrence of more severe diseases. While other researchers needed for further studies with different variables to better determine other factors associated with symptoms of Computer Vision Syndrome (CVS).